2023
DOI: 10.1088/1755-1315/1259/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nano-Fertilization and Tube Size on the Vegetative Growth and Yield Characteristics of Two Strawberry Cultivars

Salma Kh. Yassin,
Ayyub Juma Abdulrahman,
Harith Burhan Al-Din Abdulrahman

Abstract: The experiment was conducted in the unheated plastic house of the Department of Horticulture and Landscaping / College of Agriculture / University of Tikrit in the agricultural season 2021-2022. To study the effect of nano-fertilization at a concentration of 0, 1.5, 3 g, and planting with different sizes of plastic tubes with a diameter of 4, 6, and 8 inches on the vegetative growth and yield characteristics of two strawberry varieties, Fragaria ananassa Duch, Rubygem and Albion. The results showed that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It prevents them from participating interactively in the process of teaching and learning. The study conducted by Yassin et al (2014) that investigated oral communication problems among Yemeni high school EFL students in Malaysia revealed that the oral problems could be categorized into three factors. Firstly, teachers were focused on the grammatical aspects while neglecting the practical side of the language and they did not encourage their students to speak English in class.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It prevents them from participating interactively in the process of teaching and learning. The study conducted by Yassin et al (2014) that investigated oral communication problems among Yemeni high school EFL students in Malaysia revealed that the oral problems could be categorized into three factors. Firstly, teachers were focused on the grammatical aspects while neglecting the practical side of the language and they did not encourage their students to speak English in class.…”
Section: Statement Of the Problemmentioning
confidence: 99%